Pengaruh Digital Payment Gateway (OVO) Terhadap Kinerja Keuangan UMKM - Umniyah, Umniyah; Mulyadi, Dedi (Jurnal Etnik: Ekonomi-Teknik, 2023)
The use of OVO digital payments is increasing in Indonesia, especially among people who rely on MSMEs as their source of income. The aim of the research on the Effect of Digital Payment Gateway (OVO) on the Financial Performance of MSMEs is to understand the impact caused by the adoption of the use of digital payment systems such as OVO on the financial performance of MSMEs. The method used is quantitative descriptive, aiming to create an objective picture or description of a situation using numbers, starting from data collection, interpreting the data. Based on the results of the data validity test which includes the validity test and reliability test, it is known that the data validity test for each variable is the digital payment variable (X) and the MSME financial performance variable (Y). has a Sig(2-tailed) value that is smaller than the specified error significance value or error level so that the validity test is fulfilled. Payment gateway provides tools to process payments between costomers, businesses and banks. Payment is the most important part of a transaction between customers, businesses and banking institutions which are both used.